2010
DOI: 10.1128/jcm.00758-10
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Infection of a Steller Sea Lion ( Eumetopias jubatus ) Found in Washington State

Abstract: A pregnant sea lion stranded in the State of Washington was found to have placentitis caused by a unique strain of Coxiella burnetii. This is the first description of coxiellosis in a sea lion and suggests that exposure to sea lions may be a risk factor for contracting Q fever. CASE REPORTA pregnant adult female Steller sea lion (Stranding number WDFW2008-058) was found dead on the beach at Westhaven State Park in Westport, WA (lat 46.8981, long 124.1307), on 9 June 2008. The adult female had an estimated weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
3
48
0
Order By: Relevance
“…Synechococcus and Beggiatoaceae species can be found together in microbial mats (e.g., see reference 35), which may be favorable environments for gene exchange. Coxiella burnetii is a gammaproteobacterium only known to grow as an intracellular pathogen (36), but its DNA has been detected by PCR in a variety of terrestrial (37) and marine (38) environments, and one strain has been found infecting a Steller sea lion (39), making genetic exchange between Coxiella and Beggiatoaceae a possibility. As more giant sulfur bacterial chromosomal sequences become available, however, there may be evidence for vertical transmission of 23S rRNA introns within this group.…”
Section: Resultsmentioning
confidence: 99%
“…Synechococcus and Beggiatoaceae species can be found together in microbial mats (e.g., see reference 35), which may be favorable environments for gene exchange. Coxiella burnetii is a gammaproteobacterium only known to grow as an intracellular pathogen (36), but its DNA has been detected by PCR in a variety of terrestrial (37) and marine (38) environments, and one strain has been found infecting a Steller sea lion (39), making genetic exchange between Coxiella and Beggiatoaceae a possibility. As more giant sulfur bacterial chromosomal sequences become available, however, there may be evidence for vertical transmission of 23S rRNA introns within this group.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative PCR to detect the IS1111a insertion sequence was performed as described previously (16). One microliter of DNA extract was used in each 25-l PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Primers targeting the IS1111a insertion sequence were used to detect C burnetii according to published procedures. 20 Samples with a crossing threshold value < 40 were considered positive. If any biological sample from an animal tested positive by PCR assay, the animal was identified as a C burnetii shedder.…”
Section: Methodsmentioning
confidence: 99%